2013
DOI: 10.1186/1472-6882-13-144
|View full text |Cite
|
Sign up to set email alerts
|

Spica prunellae promotes cancer cell apoptosis, inhibits cell proliferation and tumor angiogenesis in a mouse model of colorectal cancer via suppression of stat3 pathway

Abstract: BackgroundConstitutive activation of STAT3 is one of the major oncogenic pathways involved in the development of various types of malignancies including colorectal cancer (CRC); and thus becomes a promising therapeutic target. Spica Prunellae has long been used as an important component in many traditional Chinese medicine formulas to clinically treat CRC. Previously, we found that Spica Prunellae inhibits CRC cell growth through mitochondrion-mediated apoptosis. Furthermore, we demonstrated its anti-angiogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Rg3 is an effective chemical trace component of ginseng with a C 42 H 72 O 13 chemical formula, a molecular weight of 784 Da, and pleiotropic capabilities that include antitumor effects. Previous studies have shown that Rg3 inhibits tumor cell growth, invasion, metastasis, and neovascularization [22][23][24]. Glycolytic regulation by Rg3, a potential anticancer mechanism, has been previously reported [25,26].…”
Section: Discussionmentioning
confidence: 91%
“…Rg3 is an effective chemical trace component of ginseng with a C 42 H 72 O 13 chemical formula, a molecular weight of 784 Da, and pleiotropic capabilities that include antitumor effects. Previous studies have shown that Rg3 inhibits tumor cell growth, invasion, metastasis, and neovascularization [22][23][24]. Glycolytic regulation by Rg3, a potential anticancer mechanism, has been previously reported [25,26].…”
Section: Discussionmentioning
confidence: 91%
“…frondosa water extractTNBS-induced colitis5-ASAp.o.Reversed symptoms of colitisImmune-suppressing (reduction of TNFα, NF-κB and neutrophil influx)[21]Changlu EnemaProtein immunization induced-UCSASPi.c.Reversed inflammatory response (macro- and microscopically)No data[22]Mixed herbal preparationDNCB and acetic acid-induced colitisSASPi.c.Improvement of colitis/abolished inflammationImmune-suppressing (reduction of TNFα, INFγ and IL-6)[23]β,β-demethylacrylshikoninHCT-116 tumor xenograftNonei.p.Reduction of tumor growthinducing apoptosis of tumor cells (increasing level of Bax/ decreasing level of Bcl-2)[41]Shikunshito-KamihoDMH-induced CRCNonein diet (p.o. )Reduction of aberrant crypt fociNo data[42]SophoridineSW480 tumor xenograft5-FUi.p.Reduction of tumor growthinducing apoptosis of tumor cells ( activation of caspase-3 dependent pathways)[45]Spica Prunellae ethanol extractHT-29 tumor xenograftNonep.oReduction of tumor growthinduction apoptosis of tumor cells/inhibition of tumor angiogenesis and proliferation[46] 5-ASA 5-aminosalicylic acid, 5-FU 5-fluorouracil, 6-MP 6-mercaptopurine, CRC colorectal cancer, DMH 1,2-dimethylhydrazine, DNCB 2,4-dinitrochlorobenzene, DS dextran sodium sulfate, DX dexamethasone, i.c. intracolonic, i.p.…”
Section: Treatmentmentioning
confidence: 99%
“…To determine whether mitochondrial fission was coupled to enhanced cell division in response to Doxinduced injury, we assessed the content of PCNA. PCNA is expressed in early G1 and S phase of the cell cycle and functions in cell cycle progression, DNA replication, and DNA repair and has previously been used as a marker of cell proliferation [30,31]. There was no difference in PCNA content between groups (1644.00 AE 110.73 vs. 1543.89 AE 120.94, P = 0.562), indicating that Dox does not induce cell proliferation in livers of treated animals, at least 24 h post-treatment.…”
Section: Marker Of Cell Proliferationmentioning
confidence: 99%